Epothilone D alters normal growth, viability and microtubule dependent intracellular functions of cortical neurons in vitro - J. A. Clark (Nature Portfolio, 2020)
Abstract Brain penetrant microtubule stabilising agents (MSAs) are being increasingly validated as potential therapeutic strategies for neurodegenerative diseases and traumatic injuries of the nervous system. MSAs are historically used to treat malignancies to great effect. However, this treatment strategy can also cause adverse off-target impacts, such as the generation of debilitating neuropathy and axonal loss. Understanding of the effects that individual MSAs have on neurons of the central nervous system is still incomplete. Previous research has revealed that aberrant microtubule stabilisation can perturb many neuronal functions, such as neuronal polarity, neurite outgrowth, microtubule dependant transport and overall neuronal viability. In the current study, we evaluate the dose dependant impact of epothilone D, a brain penetrant MSA, on both immature and relatively mature mouse cortical neurons in vitro. We show that epothilone D reduces the viability, growth and complexity of immature cortical neurons in a dose dependant manner. Furthermore, in relatively mature cortical neurons, we demonstrate that while cellularly lethal doses of epothilone D cause cellular demise, low sub lethal doses can also affect mitochondrial transport over time. Our results reveal an underappreciated mitochondrial disruption over a wide range of epothilone D doses and reiterate the importance of understanding the dosage, timing and intended outcome of MSAs, with particular emphasis on brain penetrant MSAs being considered to target neurons in disease and trauma.